Studi Komparatif Kemampuan Menulis Bahasa Inggris Antara Menggunakan Strategi Belajar Induktif Dengan Deduktif - Jimmi Jimmi (LPPM Universitas Bina Sarana Informatika, 2017)
The aim of this research is to find out the comparison of narrative writing skill between inductive learning strategy and deductive learning strategy for 11th grader student of SMK Selagan. The writer uses quasi experiment method of this research. The aim of this method is to know a comparison between inductive learning strategy and deductive learning strategy which is given for students. Also this research is to know whether those learning strategies having significant effect by giving inductive learning strategy and deductive learning strategy to students. From the research done by the writer have found that the grade of students learning and analyzed by using Test Normality, then continued by the count of t test in significantly degree of α = 0, 05 by free degree nA + nB-2. The result found that t count in significantly degree is 3, 926, and T table is 1, 670, continued to be compared of it. The fact is tcount > ttable (3,926 > 1,670). It means the hypothesis is accepted and the statement said that deductive learning strategy more better and truly giving the effect toward learning English writing is definitely true.